2018
DOI: 10.1159/000479800
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Individual Determinants of Root Caries in Older People

Abstract: The aim of this study was to identify the association of the presence of root caries in older people with contextual and individual determinants using a multilevel model. Data from the National Survey of Oral Health collected in Brazil were used. A sample of older Brazilians (aged 65-74 years) was included and selected through multistage probability cluster sampling, using probability proportional to size. Contextual variables of municipalities and individual variables of older people were included. Descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…However, this association was attenuated after adjusting for other factors. This finding is consistent with other studies which found that income was not a statistically significant predictor of root caries among older individuals [23]. Although we accounted for general health insurance and whether dental insurance covered for a specific procedure, inability to afford dental care was the only statistically significant predictor of untreated root caries in the fully adjusted regression model.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, this association was attenuated after adjusting for other factors. This finding is consistent with other studies which found that income was not a statistically significant predictor of root caries among older individuals [23]. Although we accounted for general health insurance and whether dental insurance covered for a specific procedure, inability to afford dental care was the only statistically significant predictor of untreated root caries in the fully adjusted regression model.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that increasing age is associated with higher odds of having root caries. Other studies found a similar impact of age on the prevalence and severity of root caries [23]. Leake et al found that an annual addition of 0.19 on the decayed and filled root surfaces index (RDFS) is to be expected for each additional year in dentate individuals [25].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Gregory and Hyde reported that untreated root caries were present in 12% of the population aged 65-74 years old and 17% of people over 75 2) . Souza et al reported that the majority of the elderly population has at least one root caries 3) . There has long been worldwide consensus that contraction of root caries clearly increases in elderly populations 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Root caries, like coronal caries, is a biofilm/sugar-dependent disease where caries process is caused by bacteria-induced acidification as a result of metabolism of dietary carbohydrates [12]. Unlike coronal caries, lesion of RC mainly locates in the proximal supragingival sites often within 2 millimeters of cementoenamel junctions.…”
mentioning
confidence: 99%